The role of HER2 overexpression in Middle Eastern papillary thyroid cancer - Siraj, Abdul K.; Beg, Shaham; Jehan, Zeenath; Prabhakaran, Sarita; Al-Sobhi, Saif S.; Al-Dawish, Mohammed; Al-Nuaim, Abdulrahman; Al-Dayel, Fouad; Sauter, Guido; Al-Kuraya, Khawla S. (Translational Cancer Research, 2017)
Background: HER2 oncogene is involved in many cancers and serves as a prognostic marker and therapeutic target in breast cancer. The purpose of this study was to learn more on the prevalence and clinical significance of HER2 overexpression and its association with clinical parameters in Middle Eastern papillary thyroid carcinoma (PTC). Methods: A tissue microarray (TMA) containing >1,000 PTC cases with follow-up data was used. TMA sections were analyzed on protein and DNA level using immunohistochemistry and fluorescence in situ hybridization (FISH). FISH analyses were performed to look for the gain or amplifications in HER2 gene. Results: Immunohistochemical analysis showed HER2 overexpression in 19.7% of our cases. Elevated expression was almost exclusively 2+ (194 tumors) and only rarely 3+ (1 tumor). No amplification was seen by FISH. Only 3% of our cases showed mildly elevated HER2 gene copy numbers not reaching the threshold for amplification. HER2 overexpression and copy number gains were unrelated to tumor stage, metastasis, patient survival and other clinical and pathological parameters. Conclusions: Our results demonstrated that HER2 overexpression occurs at relevant frequency in papillary thyroid cancer and in the absence of gene amplification. Additionally, expression of HER2 seems to hold no clinical value as prognostic factor in PTC.